Komparasi Konsep Kafaah dalam Perspektif Imam Maliki dan Imam Syafii - Muhammad Hasyim (JURNAL PUSAKA, 2022)
This research is intended to find our about the kafa’ah concept according to Imam Maliki, then it is compared with the perspective of Imam Syafi’I. This article is conducted to study the conceptual ideas based on library research. This library research employed qualitative design. The daya were gathered via library study to arrange and interpret the concept in order promoting new point of view results. Those data can be in the forms of research paper, journal, books, and so forth which is related to the studied concept. The result of this study showed that the kafa’ah concept significantly and mostly used in the marital context. This concept shows the comparative implementation in the marital context in Indonesia, but it is actually explained to anticipate any kind of thing which may bring harm to the wife. Key words: marriage, kafaah, concept, Imam Maliki, Imam Syafii.